2009
DOI: 10.1093/brain/awp200
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus infection is not a characteristic feature of multiple sclerosis brain

Abstract: Multiple sclerosis is an inflammatory demyelinating disease of the central nervous system (CNS) that is thought to be caused by a combination of genetic and environmental factors. To date, considerable evidence has associated Epstein-Barr virus (EBV) infection with disease development. However, it remains controversial whether EBV infects multiple sclerosis brain and contributes directly to CNS immunopathology. To assess whether EBV infection is a characteristic feature of multiple sclerosis brain, a large coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
194
2
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(209 citation statements)
references
References 56 publications
4
194
2
7
Order By: Relevance
“…An increased EBV-specific CD8 1 CTL response in one MS patient [15], as well as a higher EBV-specific proliferation of CD4 1 T cell lines in two out of three MS patients [16] in the CSF as compared with paired blood, has been reported. Although these data are controversial [17], EBVinfected B cells located in neo-follicles in the meninges have been detected in patients with MS, but not with other inflammatory neurological diseases (OIND). Activated CD8 1 T cells present in the vicinity of these neo-follicles were suggestive of ongoing cytotoxic activity against EBV-infected B cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…An increased EBV-specific CD8 1 CTL response in one MS patient [15], as well as a higher EBV-specific proliferation of CD4 1 T cell lines in two out of three MS patients [16] in the CSF as compared with paired blood, has been reported. Although these data are controversial [17], EBVinfected B cells located in neo-follicles in the meninges have been detected in patients with MS, but not with other inflammatory neurological diseases (OIND). Activated CD8 1 T cells present in the vicinity of these neo-follicles were suggestive of ongoing cytotoxic activity against EBV-infected B cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that failure to control latent EBV infection in an immune privileged site, such as the subarachnoid space, could lead to recurrent intrathecal reactivation of EBV and tissue damage in the nearby grey matter 62,63 . However, a number of other studies have been unable to detect EBV in the brain or lesions of MS patients 64,65 and this remains a highly debated controversy 66 . The different results found in these studies are likely to be due to the different types of tissues and MS cases used, the variable preservation of meningeal tissues in the samples, and differences in the sensitivity of the techniques used to detect EBV infection 67 .…”
Section: Inflammatory Grey Matter Damagementioning
confidence: 99%
“…As has previously been discussed, this disparity may be a result of differences in the technical approaches used, such as different procedures of tissue processing, cutting and staining, and cohort choice. 65,101 .…”
Section: Role Of Meningeal Inflammatory Infiltratesmentioning
confidence: 99%
“…EBV was found in 90% of meningeal B-cell follicles and in perivascular cuffs of patients with MS in one study [Serafini et al 2007] but was either not found or not frequently observed in a number of subsequent studies [Willis et al 2009;Aloisi et al 2010;Lassmann et al 2010;Peferoen et al 2010;Sargsyan et al 2010;Torskilden et al 2010;Owens and Bennett, 2012;Tracy et al 2012]. Nevertheless, latent EBV infection, with residual viral particles possibly remaining chronically in B lymphocytes, may contribute to the inflammatory milieu in active MS lesions by activating an innate and adaptive immune response, including B-cell activation and proinflammatory IFNα production [Serafini et al 2010;Tzartos et al 2012;Ascherio et al 2012a].…”
Section: Genetic Risk Factors For Multiple Sclerosis Possibly Involvimentioning
confidence: 99%